2014
DOI: 10.1089/ees.2014.0031
|View full text |Cite
|
Sign up to set email alerts
|

A Multistep Chaotic Model for Municipal Solid Waste Generation Prediction

Abstract: In this study, a univariate local chaotic model is proposed to make one-step and multistep forecasts for daily municipal solid waste (MSW) generation in Seattle, Washington. For MSW generation prediction with long history data, this forecasting model was created based on a nonlinear dynamic method called phase-space reconstruction. Compared with other nonlinear predictive models, such as artificial neural network (ANN) and partial least square-support vector machine (PLS-SVM), and a commonly used linear season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…All three indices indicate that the SA based hybrid forecast outperforms the three individual models, meaning that it can be recommended for practical use. Previous report [ 15 ] has shown that chaotic model outperforms the other two models around 2%. In this study, the hybrid model raises the accuracy of chaotic model to another 1.75%.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…All three indices indicate that the SA based hybrid forecast outperforms the three individual models, meaning that it can be recommended for practical use. Previous report [ 15 ] has shown that chaotic model outperforms the other two models around 2%. In this study, the hybrid model raises the accuracy of chaotic model to another 1.75%.…”
Section: Resultsmentioning
confidence: 94%
“…Navarro-Esbri et al [ 5 ] proposed a nonlinear dynamics algorithm by state space reconstruction and a fitting function for this trajectory of the system. Song and He [ 15 ] proposed a chaotic model of nearest neighbor state space reconstruction for multistep ahead MSW generation prediction. These nonlinear dynamic system methods are based on the embedding theorem of Takens [ 16 ] and aim to rebuild the dynamic behavior from a discrete time series data with time delay and embedding dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The studies published previously indicate NARX as a most often applied method (Menezes & Barreto, 2008;Shen & Chang, 2013;Singh & Satija, 2016;Younes et al, 2015) which performs the standard neural-network-based predictors (Song & He, 2014), illustrates the nonlinear data and different relationships (Younes et al, 2015) and with recurrent connection as the most important property.…”
Section: Connection Weightsmentioning
confidence: 99%
“…Authors such as [11][12][13] use support vector machine regression (SVMR) with different strategies, with the objective of forecasting different chaotic series. It is determined that SVMR with multiple exits presents better results on iterative machines.…”
Section: Introductionmentioning
confidence: 99%